Playing Citizens: A Ludic Approach to Ocean Literacy and Heritage Education in Niteroi - Coelho, João A. L.; Silva, Diego M.; Spiegel, Carolina N. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2022)
The present short paper brings a report on gameplay workshops that were held in a municipal public school in the Brazilian city of Niterói, as part of a university-school integration project for the promotion of Ocean Literacy and Heritage Education. Called “Cultural Wave”, the project was thought for helping school students to perceive themselves as sociocultural actors in a city that is historically bonded to the ocean.